Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Handphone Merek Vivo di Sarijaya Cellular - Galuh Khairunnisa; Kadek Rai Suwena (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
Findings from research are what we're looking for: (1) the impact of brand image on buying decisions for Vivo brand mobile phones at Sarijaya Cellular Banyupoh, (2) the impact of product quality on purchasing decisions for Vivo brand mobile phones at Sarijaya Cellular Banyupoh, and (3) the impact of brand image and product quality on the decision to purchase a Vivo brand mobile phone at Sarijaya Cellular Banyupoh. This type of research is quantitative research. The population in this study were all consumers of Vivo brand mobile phones in Sarijaya Cellular Banyupoh. The number of population in this study is unknown because there is no exact data on the number of consumers of Vivo brand mobile phones in Sarijaya Cellular Banyupoh. The number of samples is 105. The sample technique used is purposive sampling technique. methods for gathering data through questionnaires and data analysis, namely multiple linear regression analysis. The SPSS 16 for Windows program is used to process the t test and F test for the hypothesis test. The study's findings show that (1) brand image has a positive and significant impact on purchasing choices for Vivo cellphones in Sarijaya cellular Banyupoh with a significance value of 0.000 <0.05, (2) product quality has a positive and significant impact on purchasing choices for Vivo cellphones in Sarijaya cellular Banyupoh with a significance value of 0.000 <0.05, and (3) brand image and product quality have a positive and significant impact on the decision to purchase of 0.000 <0.05.